Menstrual cycles during COVID-19 lockdowns: A systematic review and meta-analysis - Chao, Melissa; Menon, Carlo; Elgendi, Mohamed (Frontiers in Reproductive Health, 2022)
Coronavirus disease 2019 lockdowns produced psychological and lifestyle consequences for women of reproductive age and changes in their menstrual cycles. To our knowledge, this is the first systematic review to characterize changes in menstrual cycle length associated with lockdowns compared to non-lockdown periods. A search on May 5, 2022 retrieved articles published between December 1, 2019, and May 1, 2022, from Medline, Embase, and Web of Science. The included articles were peer-reviewed observational studies with full texts in English, that reported menstrual cycle lengths during lockdowns and non-lockdowns. Cross-sectional and cohort studies were appraised using the Appraisal tool for Cross‐Sectional Studies and the Cochrane Risk of Bias Tool for Cohort Studies, respectively. Review Manager was used to generate a forest plot with odds ratios (OR) at the 95% confidence interval (CI), finding a significant association between lockdown and menstrual cycle length changes for 21,729 women of reproductive age (OR = 9.14, CI: 3.16–26.50) with a significant overall effect of the mean (Z = 4.08, p < 0.0001). High heterogeneity with significant dispersion of values was observed (I2 = 99%, τ = 1.40, χ2 = 583.78, p < 0.0001). This review was limited by the availability of published articles that favored high-income countries. The results have implications for adequately preparing women and assisting them with menstrual concerns during lockdown periods.